Is it Worth all the Trouble? The Costs and Benefits of Antitrust Enforcement - Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The paper aims at assessing the costs and benefits of antitrust enforcement. The analysis starts with an investigation of why competition is typically worth protecting followed by a collection of empirical evidence which shows that competition actually needs protection by antitrust policy in order to hinder firms to permanently abuse market power to the detriment of consumers. Subsequently, an estimation of the costs and benefits of antitrust enforcement is undertaken for the United States and the Netherlands. The analysis differentiates between an aggregate level approach which basically focuses on deadweight losses and a disaggregate level approach which estimates the benefits of antitrust enforcement in particular antitrust cases and compares these figures with estimates of the costs of antitrust enforcement. The results basically show for the United States and the Netherlands that the realised benefits overtop the realised costs by far as long as overcharges/redistribution effects and deadweight losses are considered as welfare loss. However, if only the avoidance of deadweight losses is considered as benefit of antitrust policy, the benefits estimate for cartel and merger enforcement under a disaggregate approach cannot cover the derived cost estimate for the United States and the Netherlands.
Keywords: L40; L49; K21; 330; Antitrust policy; antitrust enforcement; cost-benefit analysis; Kartellrecht; Rechtsdurchsetzung; Wettbewerbspolitik; Kosten-Nutzen-Analyse; Wohlfahrtseffekt; Theorie; USA; Niederlande